Natural resource management to improve rural livelihoods in a natural protected area in Central Mexico: Exploring communitiesÂ´ attitudes on conservation - LÃ“PEZ-MEDELLÃN, XAVIER (Journal of Soil and Water Conservation, 2021)
This investigation examines the attitudes of 150 inhabitants of 6 different communities located in the Sierra de Huautla Biosphere Reserve, in Morelos, Mexico, regarding environmental degradation, conservation of natural resources and the biosphere reserve. The interviewees value the forest mainly because of the natural resources and the environmental services it provides, and in general, they have a positive attitude towards conservation initiatives and the establishment of the biosphere reserve, even when they do not see any benefits derived from the conservation of natural resources. Despite the existence of favorable attitudes towards conservation, this research also highlights the absence of knowledge and information within the communities regarding the objectives, projects and activities performed by the reserve, indicating a scarce intervention of the rural population in the management of the area. It is necessary to consider that the environmental attitudes are dynamics and non favorable changes can occur if some central aspects of the management of the protected area are not changed, among them, the existence of effective spaces of social participation where rural inhabitants can present their opinions, interests, demands and priorities, have access to decision making or receive compensations for the conservation costs.